Usurpação estatal da autonomia da mulher e/ou efetivação do direito fundamental à igualdade de gêneros? Um estudo bourdieusiano das modificações feitas à Lei Maria da Penha pela ação direta de inconstitucionalidade n° 4424 - Oliveira, Magali Glaucia Fávaro de (2013)
Scope of this research is central to study the changes arising from the ADI 4424 and its implications for Maria da Penha Law. Thus, this study intends to verify that the new positioning of the STF is necessary for the realization of the fundamental right to gender equality, against sexism ingrained in Brazilian society, or whether it is a usurpation of women's autonomy and their right to choose? As a final goal, we intend to demonstrate that the complaint is a strong symbolic capital in the hands of women and the inability to retract the representation made against fellow, perhaps, from the perspective of the victim, is not beneficial for the suppression of domestic violence, because it is through it that the woman has tried to succumb to his inferiority before man or placed on a level equal to his. The method used is phenomenological. For this, we use the literature, documentary and field, collecting data through interviews with semi-structured, and through observational fieldwork in stick Specializing in Family and Domestic Violence against Women Vila Velha/ES. The research is divided into four chapters. The first one deals about the procedure, origin, purpose and arguments used by the bidder in ADI 4424 and the reasons for the vote of each Minister in his trial. In the second, we analyze, from the theory of Pierre Bourdieu, the gender issue as the relationship between rulers and ruled and the effects of these constructions. The third chapter will examine male dominance in Brazilian society, giving a brief history of women in law, as well as exposing statistical date, analyzing causes some influencers that lead men to attack and weighing about the struggle between women and abuse. The last chapter features interviews with some women who were prevented from portraying the representation made against the partner in order to ascertain the reasons which led it to request the dismissal of the case as well as the feeling experienced by these negative before the court, evaluating to form some exemplary aspects discussed theoretically.